ANALISIS PENERAPAN SISTEM MANAJEMEN KESELAMATAN, KESEHATAN DAN LINGKUNGAN KERJA (SMK3L) PADA PROYEK KONSTRUKSI BANGUNAN BERTINGKAT, STUDI KASUS PEMBANGUNAN RUMAH SAKIT 16 LANTAI DI MEDAN, KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG - Miranda Simbolon; Dea Amanda Purba; Riko Jodika Tinambunan; Igor Jekkar Simalango; Rizky Simanjuntak; Yuni Yolanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of an Occupational Safety, Health, and Environment Management System (OHSMS/SMK3L) is a crucial aspect in ensuring worker safety on high-rise construction projects. This study aims to identify risky work activities, evaluate the use of Personal Protective Equipment (PPE), and assess the implementation of safety facilities on a 16-story hospital construction project in Medan. The method used was direct field observation during a three-month internship, focusing on structural work. The study results indicate various high-risk activities, including working at heights, the use of heavy equipment, electrical installations, and welding and cutting. Furthermore, several hazardous work areas were identified, such as project traffic lanes, narrow spaces, and slippery work surfaces. The use of PPE, including safety helmets, safety shoes, reflective vests, gloves, masks, and body harnesses, was generally implemented. However, discrepancies were found in the use of PPE, both in terms of completeness and standards. Safety facilities such as K3 signs, evacuation routes, fire extinguishers, and first aid kits were available, but still require improvement in quantity and placement. The conclusion of this study indicates that the implementation of SMK3L in the 16-story hospital construction project in Medan has been quite successful, but still requires improvements in supervision, worker compliance, and compliance with occupational safety standards. Optimizing the implementation of SMK3L is expected to minimize the risk of workplace accidents and create a safe, healthy, and productive work environment.